Fractional calculus-based creep model of HFRP double lap joint subjected to NaCl solution - Wang, Xiaomeng; Zhang, Juan; Wu, Qian; Petrů, Michal (Polymer testing, 2023)
Epoxy adhesion is one of the major joint technologies of FRP (Fiber Reinforced Polymer) and its long-term performance has been proven a key to its practical engineering application. In this paper, the effect of NaCl solution on the creep deformation of HFRP (Hybrid Fiber Reinforced Polymer) double lap joints is studied. To simplify the creep behavior capturing process, a fractional calculus-based creep model with a concise mathematical expression and a few fitting parameters is proposed, eliminating the need for complex series-parallel spring-dashpot combinations. The fitting results show excellent agreement with the test data, indicating the effectiveness of the proposed model. Creep leads to obvious redistribution of stress and strain of the adhesive lap joint. Stress and strain concentration can be effectively reduced by increasing the thickness of adhesive or using fillet.